Mellem kærlighed og arbejde - Omsorgsteori: Traditioner og centrale temaer - Dahl, Hanne Marlene (Kvinder, Køn & Forskning, 1997)
This is a survey of feminist theories of care, its main themes and an argument about some of its shortcomings. Various ways of understanding care and how it has been related to gender are presented. The author argues that there exists a British and a Scandinavian tradition which have had two different analytical and normative orientations. Converging traditions, which, however, neglect the theorization of knowledge, feelings and power.